2020
DOI: 10.1177/0267659120963885
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation for COVID-19 induced hypoxia: Single-center study

Abstract: Introduction: The pandemic of the coronavirus disease 2019 (COVID-19) and associated pneumonia represent a clinical and scientific challenge. The role of Extracorporeal Membrane Oxygenation (ECMO) in such a crisis remains unclear. Methods: We examined COVID-19 patients who were supported for acute respiratory failure by both conventional mechanical ventilation (MV) and ECMO at a tertiary care institution in Washington DC. The study period extended from March 23 to April 29. We identified 59 patients who requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
(53 reference statements)
0
20
0
2
Order By: Relevance
“…12 cohorts contained comparative body mass index (BMI) data for COVID-19 survivors and nonsurvivors receiving ECMO support (Figure 2). 16,[18][19][20][23][24][25][26][27][28][29] The BMI was comparable among COVID-19 survivors and nonsurvivors requiring ECMO support (mean 30.07kg/m 2 vs 30.86kg/ m 2 , SMD 0.06; 95% CI [ − 0.23, 0.34]; I 2 = 43%; P = .70).…”
Section: Study Characteristicsmentioning
confidence: 94%
See 2 more Smart Citations
“…12 cohorts contained comparative body mass index (BMI) data for COVID-19 survivors and nonsurvivors receiving ECMO support (Figure 2). 16,[18][19][20][23][24][25][26][27][28][29] The BMI was comparable among COVID-19 survivors and nonsurvivors requiring ECMO support (mean 30.07kg/m 2 vs 30.86kg/ m 2 , SMD 0.06; 95% CI [ − 0.23, 0.34]; I 2 = 43%; P = .70).…”
Section: Study Characteristicsmentioning
confidence: 94%
“…According to nine studies, the rate of bleeding complications was lower (32% vs 59%; OR 0.36; 95% CI 0.20-0.67;I 2 = 17%; P = .001) among COVID-19 survivors requiring ECMO support than nonsurvivors (Figure 5). [17][18][19][20][21][22]25,28,29 Five studies reported that COVID-19 survivors and nonsurvivors requiring ECMO support had comparable (43% vs 35%; OR 1.35; 95% CI 0.87-2.11;I 2 = 0%; P = .18) secondary infections rate (Figure 5). 18,20,25,28,29 Lastly, the rate of thromboembolism was similar (32% vs 30%; OR 1.89; 95% CI 0.55-6.47;I 2 = 77%; P = .31) between survivors and nonsurvivors of COVID-19 requiring ECMO support in four studies (Figure 5).…”
Section: Total Days On Mechanical Ventilation (Mv) Before Ecmo Support Initiation and Ecmo Durationmentioning
confidence: 99%
See 1 more Smart Citation
“…1). [5,6,[12][13][14][15][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] After excluding 11 studies with overlapping information, we included twenty-two retrospective observational studies with 1896 patients in the meta-analysis. There were 20 single centre studies and two registry reports (Tables 1 and 2).…”
Section: Study Details and Demographicsmentioning
confidence: 99%
“…Refractory hypoxemia may develop, occasionally warranting the consideration of alternative strategies such as veno-venous extracorporeal membrane oxygenation (VV-ECMO). 1,2 Careful patient selection for VV-ECMO is a challenging task, as recently pointed out. 3 This raises important questions concerning the outcomes of patients who are not eligible for ECMO.…”
mentioning
confidence: 99%